Development of Sharia Venture Capital in Indonesia (Case Study, PT PMN Syariah) - Smitasari, Daneswara; Cupian, Cupian (PT Literasi Nusantara Publisher, 2023)
Venture capital is a form of a non-bank financial institution which is an alternative financing that offers more effective and efficient incentives in developing entrepreneurial businesses. This article aims to discover the Indonesian people's development and awareness regarding Sharia venture capital in the case study of PT. PMN Syariah and how big is the role of Islamic venture capital in developing MSMEs with descriptive qualitative method.